2014
DOI: 10.1589/jpts.26.595
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Cervical Repositioning Errors According to Smartphone Addiction Grades

Abstract: [Purpose] The purpose of this study was to compare cervical repositioning errors according to smartphone addiction grades of adults in their 20s. [Subjects and Methods] A survey of smartphone addiction was conducted of 200 adults. Based on the survey results, 30 subjects were chosen to participate in this study, and they were divided into three groups of 10; a Normal Group, a Moderate Addiction Group, and a Severe Addiction Group. After attaching a C-ROM, we measured the cervical repositioning errors of flexio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 17 publications
(18 reference statements)
1
53
0
3
Order By: Relevance
“…Obviously, prolong neck bending will alter cervical curvature and creating undue stress and experiencing constant discomfort over adjacent structure 11 . Even though, there is moderately weak correlation between addiction and upper back, arm discomfort the results is consistent with previous study 12,13,14 . The limitation of this study is the small respondent size which represents at one shopping mall in Kuala Lumpur.…”
Section: Discussionsupporting
confidence: 92%
“…Obviously, prolong neck bending will alter cervical curvature and creating undue stress and experiencing constant discomfort over adjacent structure 11 . Even though, there is moderately weak correlation between addiction and upper back, arm discomfort the results is consistent with previous study 12,13,14 . The limitation of this study is the small respondent size which represents at one shopping mall in Kuala Lumpur.…”
Section: Discussionsupporting
confidence: 92%
“…reported that while using a smartphone, individuals with minor neck pain bent their neck slightly more than those without neck pain, although the causal relationship could not be identified . In this regard, Lee and Seo (2014) noted that a higher degree of smartphone addition may lead to a reduction in the ability to recognize neck posture (Lee and Seo, 2014). These studies suggest that the use of a smartphone can impair the sensory ability to recognize neck posture, thereby becoming a factor that causes pain by bending the neck at a higher angle.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…The joint position sense is crucial for head-on-trunk orientation [21]. Lee and Seo [38] investigated the impact of addiction to smartphone use on cervical repositioning error. They found that the severe addiction group showed the largest repositioning error.…”
Section: Discussionmentioning
confidence: 99%